ANALYZING SCIENTIFIC PRINCIPLES IN THE KURDISH DICTIONARY: JUDY DICTIONARY AS A SAMPLE - ISMAIL RAJAB, DR.SULAIMAN; AHMED, DR.ARAAL; QASIM, DR.HUDAABDULQADER (Journal of Duhok University, 2019)
Lexicology is important for any language in order to know that language and preserve it particularly when the dictionary is written in two languages and this is one of the important requirements to compile a dictionary.Besides tackling lexicology, types of dictionaries, showing the scientific fundamentals of dictionaries, this research is an academic attempt to identify dictionary shortcoming in terms of form and content in Kurdish in order to be a basic dictionaries in Kurdish. Thus, a two language dictionary was taken as a sample, i.e. Judi dictionary.